TAHAPAN PEMBERDAYAAN MASYARAKAT DALAM PENGEMBANGAN DESA WISATA MELUNG KECAMATAN KEDUNGBANTENG KABUPATEN BANYUMAS - Fariza Indar Inayah; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Melung Tourism Village is one of the tourism villages in Banyumas Regency that has considerable potential for nature, education, and cultural tourism. The development of this tourism village is directed through a community empowerment approach to improve the welfare of residents in a sustainable manner. However, its implementation has not been fully optimal. The problems faced include low community participation, limited human resources, and weak local institutional capacity. These conditions indicate a gap between the potential of the tourism village and the implementation of community empowerment in the field. This study aims to describe and analyze the stages of community empowerment in the development of Melung Tourism Village, as well as to identify the driving and inhibiting factors. This study uses a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. The results show that community empowerment has been carried out through the stages of awareness, capacity building, and empowerment, but has not been optimal. The driving factors include natural resource potential, village institutional support, and policies, while the inhibiting factors include budget constraints, uneven human resource quality, limited facilities and infrastructure, and institutional capacity that is not yet independent. This study concludes that strengthening community and institutional capacity is key to the sustainability of Melung Tourism Village development.